Kinerja Keuangan Perusahaan Asuransi Jiwa Konvensional di Indonesia Periode 2015-2018 - Ely Siswanto; Raudhotul Miul Hasanah (Jurnal Ekonomi Modernisasi, 2019)
This research aims to analyze the effect of financial indicator such as premium income, investment returns, volume of capital, loss ratio, operating expenses and risk based capital on the profitability (ROA) of conventional life insurance companies during the first quarter of 2015 until the third quarter of 2018. This research uses premium income, investment returns, volume of capital, loss ratio, operating expenses and risk based capital as independent variables and the dependent variable is Return On Assets, and joint venture alliance strategies as a control variable. The population of data is conventional life insurance companies in Indonesia during 2015 until 2018. This research used a purposive sampling technique, it was found that 14 companies met the sample criteria. The analysis model uses regression analysis. The research results show that premium income has a positive significant effect on ROA, the volume of capital has a positive significant effect on ROA and operating expenses have a negative significant effect on ROA. While investment returns, loss ratios and risk based capital, and joint venture alliance strategies do not have a significant effect on ROA. Meanwhile, a joint venture alliance strategies are not significant in influencing the relationship of independent variables to ROA. Further research is recommended to conduct a different test of the financial performance of insurance companies, national life insurance companies and joint venture life insurance companies.